The application of Eulerian laser Doppler vibrometry to the on-line condition monitoring of axial-flow turbomachinery blades - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.